Entrepreneurial Behavior: A Reconceptualization and Extension Based on Identity Theory - Gruber, Marc; MacMillan, Ian C. (Strategic Entrepreneurship Journal, 2017)
Research summary Entrepreneurial behavior is core to our understanding of entrepreneurship. Yet, research progress is hindered because most studies adopt a traditional perspective of the construct that is embedded in economic rationality and focused on for‐profit ventures. Drawing on identity theory, we propose a reconceptualization that emphasizes the “identity relevance” of entrepreneurial behaviors, allows for different meanings that founders associate with entrepreneurship, and views founders as behaving in ways that they deem appropriate. Importantly, this perspective accounts for the behaviors not only of entrepreneurs who start ventures strictly out of economic self‐interest, but also those who launch ventures because of concern for others—either in their community or in society at large. We elaborate on this argument and discuss ideas for future research. Managerial summary We suggest that a concept of entrepreneurial behavior predicated on the purely rent‐seeking entrepreneur ignores the increasing, and increasingly important, number of entrepreneurs who start enterprises for more than pure economic rent generation. Using identity theory permits us to parse modern entrepreneurs into three major types, namely the traditional seeker of rent, the entrepreneur who seeks to aid the community, and the entrepreneur who seeks to aid society at large. We show that using an identity perspective on entrepreneurial behavior allows us to explain very different economic and social outcomes by entrepreneur social identity type and posit the influence of entrepreneurial types in society on the evolution of a macroeconomic cycle. Copyright © 2017 Strategic Management Society.